UMPSA advances global networks at EAIE 2025 and official visit to Chalmers University of Technology, Sweden - Nur Ezzati, Mohd Nasir (UMPSA, 2025)
GOTHENBURG, SWEDEN, 9 September 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) participated in the European Association for International Education (EAIE) 2025 Conference in Gothenburg, Sweden, with a mission to strengthen global academic and research collaborations.